Event-triggered sampled–data fuzzy secure control for nonlinear parabolic PDE systems subject to stochastic actuator failures and deception attacks - Zhao, Feng-Liang; Wang, Zi-Peng; Li, Fangyu; Qiao, Junfei; Wu, Huai-Ning (Fuzzy sets and systems, 2025)
Under spatially point measurements (SPMs), this paper addresses event-triggered sampled-data (ETSD) fuzzy secure control for nonlinear space-varying parabolic partial differential equation (PDE) systems with stochastic actuator failures and deception attacks. Initially, a T-S fuzzy PDE model is presented to exactly describe the nonlinear space-varying parabolic PDE systems subject to stochastic actuator failures and deception attacks. Secondly, in order to reduce the unnecessary sampled-data and adapt to the variation of system dynamics subject to stochastic actuator failures and deception attacks, an ETSD fuzzy secure control scheme is proposed under SPMs. Then, by constructing an appropriate Lyapunov functional, the mean square exponential stability conditions of closed-loop nonlinear space-varying parabolic PDE systems via spatial linear matrix inequalities (SLMIs) are presented. Furthermore, to solve SLMIs, the ETSD fuzzy secure control design problem for nonlinear space-varying parabolic PDE systems under SPMs with stochastic actuator failures and deception attacks is formulated as an linear matrix inequality feasibility problem. Finally, simulation results of two examples are presented to demonstrate the effectiveness of the proposed design approach.